Adhesion and whitening efficacy of P11-4 self-assembling peptide and HAP suspension after using NaOCl as a pre-treatment agent - Niloofar Hojabri; Karl-Heinz Kunzelmann (BMC, 2022)
Abstract Background This study evaluated the adhesion and whitening efficacy of a mixture of hydroxyapatite and P11-4 self-assembling peptide (HAP-peptide) on bovine enamel after pre-treatment with low-concentrated sodium hypochlorite (NaOCl). Methods Fifty-two caries-free bovine incisors were selected. 50 teeth were randomly allocated to five groups (n = 10). The first group was treated with a mixture of 6.25 wt% HAP and 5 ml P11-4 peptide, using NaOCl 3% as pre-treatment. Second, third and fourth groups were treated with 6.25 wt% HAP, 5 ml P11-4 peptide, and NaOCl 3%, respectively. In the fifth group, only water was applied (control group). The color of samples was measured using a spectrophotometer (USB4000-VIS-NIR-ES, Ostfildern, Germany). To evaluate color changes, ΔE values were statistically analyzed. Finally, adherence of HAP particles on two enamel surfaces with and without pre-treatment with NaOCl was analyzed with SEM. Results It was observed that the ΔE of the HAP-peptide suspension after pre-treatment with NaOCl was significantly stronger than the control group. In contrast, the overall color changes of separate applications of HAP, peptide, and NaOCl did not differ notably from the control group. SEM observations confirmed that pre-treatment with NaOCl resulted in a more pronounced coverage of HAP on the enamel surface. Conclusions Pre-treatment with a low-concentrated NaOCl enhanced the adherence of the HAP layer on the enamel surface, resulting in a stronger whitening effect. Trial registration The peptide-HAP suspension is effective in improving tooth whiteness.